A Retrospective Multicenter Study Comparing Speech Perception Outcomes for Bilateral Implantation and Bimodal Rehabilitation. Issue 4 (July 2015) - Blamey, Peter J.; Maat, Bert; Başkent, Deniz; Mawman, Deborah; Burke, Elaine; Dillier, Norbert; Beynon, Andy; Kleine-Punte, Andrea; Govaerts, Paul J.; Skarzynski, Piotr H.; Huber, Alexander M.; Sterkers-Artières, Françoise; et al.
Abstract : Objectives: To compare speech perception outcomes between bilateral implantation (cochlear implants [CIs]) and bimodal rehabilitation (one CI on one side plus one hearing aid [HA] on the other side) and to explore the clinical factors that may cause asymmetric performances in speech intelligibility between the two ears in case of bilateral implantation. Design: Retrospective data from 2247 patients implanted since 2003 in 15 international centers were collected. Intelligibility scores, measured in quiet and in noise, were converted into percentile ranks to remove differences between centers. The influence of the listening mode among three independent groups, one CI alone (n = 1572), bimodal listening (CI/HA, n = 589), and bilateral CIs (CI/CI, n = 86), was compared in an analysis taking into account the influence of other factors such as duration of profound hearing loss, age, etiology, and duration of CI experience. No within-subject comparison (i.e., monitoring outcome modifications in CI/HA subjects becoming CI/CI) was possible from this dataset. Further analyses were conducted on the CI/CI subgroup to investigate a number of factors, such as implantation side, duration of hearing loss, amount of residual hearing, and use of HAs that may explain asymmetric performances of this subgroup. Results: Intelligibility ranked scores in quiet and in noise were significantly greater with both CI/CI and CI/HA than with a CI-alone group, and improvement with CI/CI (+11% and +16% in quiet and in noise, respectively) was significantly better than with CI/HA (+6% and +9% in quiet and in noise, respectively). From the CI/HA group, only subjects with ranked preoperative aided speech scores >60% performed as well as CI/CI participants. Furthermore, CI/CI subjects displayed significantly lower preoperative aided speech scores on average compared with that displayed by CI/HA subjects. Routine clinical data available from the present database did not explain the asymmetrical results of bilateral implantation. Conclusions: This retrospective study, based on basic speech audiometry (no lateralization cues), indicates that, on average, a second CI is likely to provide slightly better postoperative speech outcome than an additional HA for people with very low preoperative performance. These results may be taken into consideration to refine surgical indications for CIs. Abstract : Retrospective data from 2247 patients implanted since 2003 in 15 international centers were analyzed to assess which binaural hearing restoration provides better outcome between bilateral cochlear implants (CIs) and bimodal listening (one CI on one side + one hearing aid [HA] on the other side). A small but significant difference was observed in terms of speech understanding in favor of bilateral CIs compared to bimodal rehabilitation for people with low pre-operative performance. These results may be taken into consideration to refine surgical indications for CIs.